Efektywność działań innowacyjnych przedsiębiorstwa w relacjach z klientami na przykładzie handlu elektronicznego w Polsce - Brzózka, Monika (Efficiency of Innovative Operation in Enterprise - Client Relationship on the Example of Electronic Commerce in Poland, 2006)
Electronic commerce is fastly developing domain of business in Poland. This modem form of relationship between enterprise and clients becomes more and more popular. Infrastructural conditions and those which flows from the business environment do not make easier selling and doing business on-line. However, it is worth to take new challenges to cope with requirements of market and present times. In article, author presents most important barriers in functioning of electronic commerce in Poland and benefits from this domain of business.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 27-35